Influenza activity in Kenya, 2007–2013: timing, association with climatic factors, and implications for vaccination campaigns - Emukule, Gideon O. (Influenza Other Respir Viruses, 2016)
BACKGROUND: Information on the timing of influenza circulation remains scarce in Tropical regions of Africa. OBJECTIVES: We assessed the relationship between influenza activity and several meteorological factors (temperature, specific humidity, precipitation) and characterized the timing of influenza circulation and its implications to vaccination strategies in Kenya. METHODS: We analyzed virologically confirmed influenza data for outpatient influenza‐like illness (ILI), hospitalized for severe acute respiratory infections (SARI), and cases of severe pneumonia over the period 2007–2013. Using logistic and negative binomial regression methods, we assessed the independent association between climatic variables (lagged up to 4 weeks) and influenza activity. RESULTS: There were multiple influenza epidemics occurring each year and lasting a median duration of 2–4 months. On average, there were two epidemics occurring each year in most of the regions in Kenya, with the first epidemic occurring between the months of February and March and the second one between July and November. Specific humidity was independently and negatively associated with influenza activity. Combinations of low temperature (<18°C) and low specific humidity (<11 g/kg) were significantly associated with increased influenza activity. CONCLUSIONS: Our study broadens understanding of the relationships between seasonal influenza activity and meteorological factors in the Kenyan context. While rainfall is frequently thought to be associated with influenza circulation in the tropics, the present findings suggest low humidity is more important in Kenya. If annual vaccination were a component of a vaccination strategy in Kenya, the months of April to June are proposed as optimal for associated campaigns.